Sanitary quality of broiler litter reused - Maria de F. A. Vieira; Ilda de F. F. Tinoco; Bernadete M. dos Santos; Keles R. A. Inoue; Múcio A. dos S. A. Mendes (Engenharia Agrícola, 2015)
ABSTRACT Considering the importance of the substrate to bedding in the poultry industry in Brazil, and the enormous pressure on environmental management as to the correct use and management of the waste generated by the production sector, this study aimed to analyze the effect of reuses of two types of litter on sanitary qualities and productive performance of broilers. The study was conducted with litter from 32 different broiler houses, two types of substrates and four cycles of reuses. The litter sanitary quality was verified by the identification of the presence of Escherichia coli and Salmonellaspp. and the incidence of footpad dermatitis. It was observed that the coffee hulls litter presented a reduction of 28.61 percentage points in the probability of occurrence of Salmonella spp when compared to the wood shavings litter, nevertheless, no statistical difference was observed on bacterial occurrence with Salmonella spp. for litter of different types or numbers of reutilization. The presence of Escherichia coli was detected in litter of all cycles, for both types of substrate. The occurrence of footpad lesions was detected for both types of litter, and was influenced by the number of reutilization cycles of the litter. The degree of incidence was detected only for the litter with coffee hull in which there was an increase of 30% between the first and second reuse from which tended to stabilize.